Resistive Switching Behavior of Magnesium Zirconia Nickel Nanorods - Su, Tzu-Han (Materials (Basel), 2020)
To effectively improve the uniformity of switching behavior in resistive switching devices, this study developed magnesium zirconia nickel (MZN) nanorods grown on ITO electrodes through hydrothermal method. The field emission scanning electron microscope image shows the NR formation. Al/MZN NR/ITO structure exhibits forming-free and bipolar resistive switching behaviors. MZN NRs have relatively higher ON/OFF ratio and better uniformity compared with MZN thin film. The superior properties of MZN NRs can be attributed to its distinct geometry, which leads to the formation of straight and extensible conducting filaments along the direction of MZN NR. The results suggest the possibility of developing sol–gel NR-based resistive memory devices.